High-performance composite modified asphalt and preparation method thereof

By introducing maleic anhydride grafted styrene thermoplastic elastomers and reactive resins into the asphalt, a dynamic covalent bonding network structure is formed, which solves the adaptability of the asphalt matrix under load and temperature changes. The problem of insufficient problems has significantly improved the performance and service life of asphalt.

CN119264691APending Publication Date: 2025-01-07CHONGQINGSHI ZHIXIANG PAVING TECH ENG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411654299.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Under the superposition effect of load, temperature and time, the existing asphalt matrix leads to insufficient adaptability to the deformation of the base surface and the temperature amplitude, resulting in structural damage such as cracking, cracking, pits, etc. in bridge paving, and its service life and design requirements. The difference is quite different.

Method used

High-performance composite modified asphalt is composed of road petroleum asphalt, maleic anhydride grafted styrene thermoplastic elastomer, mineral oil, dendrimer with high density hydrogen bonding, reactive resin and anti-aging agent, and dynamic co-combination The bonding network structure of valence bond-hydrogen bond improves interface compatibility and toughness, and adds reactive resin to improve the high-temperature and low-temperature performance of asphalt.

Benefits of technology

It significantly improves the construction ease, thermal oxygen aging degree and fatigue life of asphalt, solves the technical problem of coordinated long-term deformation of steel bridge deck and paving layer under high strain and large temperature difference, and extends the service life of asphalt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264691A_ABST
    Figure CN119264691A_ABST
Patent Text Reader

Abstract

Belonging to the technical field of road material preparation, the invention discloses a high performance composite modified asphalt, which is composed of 100 parts of road petroleum asphalt, 3-9 parts of maleic anhydride grafted styrene thermoplastic elastomer, 2-6 parts of mineral oil, 1-5 parts of high density hydrogen bond dendritic molecule, 5-20 parts of reactive resin, and 0.3-1.2 parts of anti-aging agent. A dynamic covalent bond-hydrogen bond bonding network structure is constructed based on maleic anhydride grafted styrene thermoplastic elastomer-reactive resin-tannic acid modification, so that the interfacial compatibility of asphalt and a modifier in a wide temperature range is remarkably improved, and the fluidity transition temperature window of the modified asphalt is reduced; the high toughness of the mixture is ensured, the construction workability of the mixture is improved, and the thermo-oxidative aging degree is reduced; meanwhile, the high-temperature performance, the low-temperature performance and the fatigue life are improved, and the technical problem of synergistic lasting deformation of the steel bridge deck and the pavement layer under high strain and large temperature difference is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road materials, and in particular relates to a high-performance composite modified asphalt and a preparation method thereof. Background Art

[0002] Asphalt pavement, as the weakest structure in the bridge system, is the biggest obstacle restricting the project life and traffic capacity, and is also the core of bridge opening and safe operation.

[0003] Today, the quality and lifespan of civil engineering projects have been greatly improved, but early diseases of bridge deck pavement occur frequently and the service life is far from the design requirements. This is mainly due to the fact that the asphalt matrix is ​​a viscoelastic material. After considering the superposition effects of load, temperature and time, its ability to adapt to base deformation and temperature fluctuations is severely limited, resulting in tensile damage, and various types of structural damage such as cracking, potholes, and delamination. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high-performance composite modified asphalt and a preparation method thereof to solve the above-mentioned problems.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a high-performance composite modified asphalt, which consists of 100 parts of road petroleum asphalt, 3-9 parts of maleic anhydride grafted styrene thermoplastic elastomer, 2-6 parts of mineral oil, 1-5 parts of high-density hydrogen bond dendritic molecules, 5-20 parts of reactive resin and 0.3-1.2 parts of anti-aging agent.

[0007] Furthermore, the maleic anhydride grafted styrene-based thermoplastic elastomer is at least one of MAH grafted SEBS and MAH grafted SBS, or a mixture of the two, and the grafting rate is not less than 1.2%.

[0008] Furthermore, the dendritic molecules with high-density hydrogen bonds are tannic acid with a purity of not less than 98%.

[0009] Furthermore, the reactive resin is composed of a main agent and a curing agent, wherein the main agent is composed of a polyurethane-modified epoxy resin, a glycidyl ester and a hyperbranched epoxy resin in a mass ratio of 50-90:10-30:10-30; the polyurethane-modified epoxy resin is at least one of EPU-133, EPU-133L and EPU-133S; the glycidyl ester is at least one of diglycidyl phthalate, diglycidyl dimer acid, diglycidyl sebacic acid and diglycidyl azelaic acid; the hyperbranched epoxy resin has an epoxide value of 0.15-0.2 mol / 100g and a molecular weight of 3000-4000.

[0010] Furthermore, the curing agent is composed of a long carbon chain unsaturated primary amine, an aromatic amine and an amino-terminated hyperbranched polyamide in a mass ratio of 70-120:10-30:10-20; the long carbon chain unsaturated primary amine is a cis-oleyl primary amine; the aromatic amine curing agent is one or more of 4,4'-dithiodiphenylamine, bis(2-aminophenyl) disulfide, and 4,4'-diaminodiphenyl disulfide; the amino number of the amino-terminated hyperbranched polyamide is 3-15 mol, and the molecular weight is 300-2000.

[0011] Furthermore, the anti-aging agent is a composite of an ultraviolet absorber and a hindered amine light stabilizer, and the mass ratio of the two is 1:1; the ultraviolet absorber is at least one of UV531, UV24, UV284 or UV49; and the hindered amine light stabilizer is HS-944.

[0012] Furthermore, it also includes a method for preparing a high-performance composite modified asphalt, comprising the following steps:

[0013] S1. After heating the road petroleum asphalt, add mineral oil and maleic anhydride grafted styrene thermoplastic elastomer, shear for 60-90 minutes, continue to add high-density hydrogen bond dendritic molecules and anti-aging agents, and continue stirring for 30-60 minutes, keeping the temperature at 170-185°C to prepare mixture A;

[0014] S2, polyurethane modified epoxy resin, glycidyl ester and hyperbranched epoxy resin are mixed uniformly to prepare a main agent; long carbon chain unsaturated primary amine, aromatic amine and amino-terminated hyperbranched polyamide are prepared as a curing agent; the main agent and the curing agent are mixed uniformly to prepare a reactive resin;

[0015] S3. Add the reactive resin into mixture A in proportion and stir for 5-15 minutes to obtain high-performance composite modified asphalt.

[0016] Furthermore, in the step S1, the road petroleum asphalt is heated to 170-180°C; the shear rate after adding mineral oil and maleic anhydride grafted styrene thermoplastic elastomer and mixing is 3000-4000r / min.

[0017] Furthermore, in step S2, the mixing temperature of the main agent and the curing agent is 30-50°C.

[0018] Furthermore, in step S3, the reaction temperature of the reactive resin and the mixture A is 170-185°C.

[0019] The beneficial effects of the present invention are:

[0020] 1. In the present invention, maleic anhydride grafted styrene thermoplastic elastomer can regulate the phase structure of the modifier and road asphalt. The phenolic hydroxyl group and phenol ring reaction sites rich in tannic acid can form effective high-density interaction points at the interface, and together with the reactive resin-maleic anhydride grafted styrene thermoplastic elastomer, a dynamic covalent bond-hydrogen bond bonding network structure is constructed in the asphalt system, which significantly improves the interfacial compatibility between asphalt and the modifier in a wide temperature range, reduces the temperature window of the fluidity transition of the modified asphalt, and can also ensure the high toughness of the mixture.

[0021] 2. The high-performance composite modified asphalt of the present invention significantly improves the construction and workability of the mixture and reduces the degree of thermal oxidation aging; it also improves the high-temperature performance, low-temperature performance and fatigue life, and solves the technical problem of coordinated and persistent deformation of the steel bridge deck and the pavement layer under high strain and large temperature difference.

[0022] 3. The preparation method of the high-performance composite modified asphalt of the present invention is simple, the raw materials are easily available, and it can be applied on a large scale in practical applications.

[0023] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the purpose, technical solution and beneficial effects of the invention clearer, the present invention provides the following drawings for illustration:

[0025] Figure 1 This is a scanning electron microscope of the high-performance composite modified asphalt of the present invention.

[0026] Figure 2 This is an atomic force microscope of the high-performance composite modified asphalt of the present invention. DETAILED DESCRIPTION

[0027] A high-performance composite modified asphalt and a preparation method thereof.

[0028] Example 1

[0029] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of maleic anhydride grafted styrene thermoplastic elastomer (MAH grafted SEBS), and shear at 4000r / min for 60min; then continue to add 1 part of high-density hydrogen-bonded dendritic molecules (tannic acid, purity 98.5%) and 0.3 parts of anti-aging agent (complex of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30min to obtain mixture A;

[0030] S2. At 30°C, polyurethane modified epoxy resin (EPU-133), glycidyl ester (diglycidyl phthalate) and hyperbranched epoxy resin (epoxy value of 0.15 mol / 100 g, molecular weight of 3350) are mixed uniformly in a mass ratio of 50:10:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine), aromatic amine (4,4'-dithiodiphenylamine) and amino-terminated hyperbranched polyamide (amino number of 5 mol, molecular weight of 830) are mixed in a mass ratio of 70:10:10 to prepare a curing agent; the main agent and the curing agent are then stirred uniformly to obtain a reactive resin;

[0031] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare high-performance composite modified asphalt.

[0032] Example 2

[0033] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of maleic anhydride grafted styrene thermoplastic elastomer (MAH grafted SEBS), and shear at 4000r / min for 60min; then continue to add 1 part of high-density hydrogen-bonded dendritic molecules (tannic acid, purity 98.5%) and 0.3 parts of anti-aging agent (complex of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30min to obtain mixture A;

[0034] S2. At 30°C, polyurethane modified epoxy resin (EPU-133L), glycidyl ester (a mixture of dimer acid diglycidyl ester and azelaic acid diglycidyl ester) and hyperbranched epoxy resin (epoxy value of 0.18 mol / 100 g, molecular weight of 3600) are mixed uniformly in a mass ratio of 90:30:30 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine), aromatic amine (a mixture of bis(2-aminophenyl) disulfide and 4,4'-diaminodiphenyl disulfide) and amino-terminated hyperbranched polyamide (amino number of 10 mol, molecular weight of 1300) are mixed in a mass ratio of 120:30:20 to prepare a curing agent; the main agent and the curing agent are stirred uniformly to obtain a reactive resin;

[0035] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare high-performance composite modified asphalt.

[0036] The difference between Example 2 and Example 1 is that the types and proportions of the raw materials for preparing the main agent and the curing agent are different, but both are within the scope of the present invention.

[0037] Example 3

[0038] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 5 parts of mineral oil and 6 parts of maleic anhydride grafted styrene thermoplastic elastomer (MAH grafted SEBS), and shear at 4000r / min for 60min; then continue to add 5 parts of high-density hydrogen-bonded dendritic molecules (tannic acid, purity 98.5%) and 1.1 parts of anti-aging agent (complex of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30min to obtain mixture A;

[0039] S2. At 30°C, polyurethane modified epoxy resin (EPU-133), glycidyl ester (diglycidyl phthalate) and hyperbranched epoxy resin (epoxy value of 0.15 mol / 100 g, molecular weight of 3350) are mixed uniformly in a mass ratio of 85:28:12 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine), aromatic amine (4,4'-dithiodiphenylamine) and terminal amino hyperbranched polyamide (amino number of 5 mol, molecular weight of 830) are mixed in a mass ratio of 70:10:10 to prepare a curing agent; the main agent and the curing agent are then stirred uniformly to obtain a reactive resin;

[0040] S3. At 170°C, add 10 parts of reactive resin into mixture A and continue stirring for 5 minutes to prepare high-performance composite modified asphalt.

[0041] The difference between Example 3 and Example 1 is that 100 parts of road petroleum asphalt are used as the basis, and the parts and selections of the remaining materials are different, but all are within the scope of the present invention.

[0042] Example 4

[0043] S1. Heat 100 parts of road petroleum asphalt to 180°C, add 2 parts of mineral oil and 4 parts of maleic anhydride grafted styrene thermoplastic elastomer (MAH grafted SEBS), and shear at 3000r / min for 90min; then continue to add 1 part of high-density hydrogen-bonded dendritic molecules (tannic acid, purity 98.5%) and 0.3 parts of anti-aging agent (complex of UV531 and HS-944, mass ratio 1:1), and keep stirring at 185°C for 30min to obtain mixture A;

[0044] S2. At 50°C, polyurethane modified epoxy resin (EPU-133), glycidyl ester (diglycidyl phthalate) and hyperbranched epoxy resin (epoxy value of 0.15 mol / 100 g, molecular weight of 3350) are mixed uniformly in a mass ratio of 50:10:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine), aromatic amine (4,4'-dithiodiphenylamine) and terminal amino hyperbranched polyamide (amino number of 5 mol, molecular weight of 830) are mixed in a mass ratio of 70:10:10 to prepare a curing agent; the main agent and the curing agent are then stirred uniformly to obtain a reactive resin;

[0045] S3. At 185°C, 8 parts of reactive resin were added to mixture A and stirred for 10 minutes to prepare high-performance composite modified asphalt.

[0046] The difference between Example 4 and Example 1 is that the parameter conditions of each step during the preparation are different, but all are within the scope of the present invention.

[0047] In order to demonstrate the superiority of the raw materials and proportions of the present invention, Comparative Examples 1 to 4 are set up here.

[0048] Comparative Example 1

[0049] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of styrene-based thermoplastic elastomer (SEBS), and shear at 4000 r / min for 60 minutes; then continue to add 0.3 parts of anti-aging agent (composite of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30 minutes to obtain mixture A;

[0050] S2. At 30°C, polyurethane modified epoxy resin (EPU-133), glycidyl ester (diglycidyl phthalate) and hyperbranched epoxy resin (epoxy value of 0.15 mol / 100 g, molecular weight of 3350) are mixed uniformly in a mass ratio of 50:10:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine), aromatic amine (4,4'-dithiodiphenylamine) and amino-terminated hyperbranched polyamide (amino number of 5 mol, molecular weight of 830) are mixed in a mass ratio of 70:10:10 to prepare a curing agent; the main agent and the curing agent are then stirred uniformly to obtain a reactive resin;

[0051] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare asphalt.

[0052] The difference between Comparative Example 1 and Example 1 is that the styrene-based thermoplastic elastomer replaces the maleic anhydride-grafted styrene-based thermoplastic elastomer, and no dendritic molecules with high-density hydrogen bonds are added.

[0053] Comparative Example 2

[0054] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of styrene-based thermoplastic elastomer (SEBS), and shear at 4000 r / min for 60 minutes; then continue to add 1 part of high-density hydrogen-bonded dendritic molecules (tannic acid, purity 98.5%) and 0.3 parts of anti-aging agent (complex of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30 minutes to obtain mixture A;

[0055] S2. At 30°C, polyurethane modified epoxy resin (EPU-133) and glycidyl ester (diglycidyl phthalate) were mixed evenly in a mass ratio of 50:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine) and aromatic amine (4,4'-dithiodiphenylamine) were mixed in a mass ratio of 70:10 to prepare a curing agent; the main agent and the curing agent were then stirred evenly to obtain a reactive resin;

[0056] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare asphalt.

[0057] The difference between Comparative Example 2 and Example 1 is that the maleic anhydride-grafted styrene thermoplastic elastomer is replaced by the styrene thermoplastic elastomer, and the hyperbranched epoxy resin and the amino-terminated hyperbranched polyamide are not added.

[0058] Comparative Example 3

[0059] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of maleic anhydride grafted styrene thermoplastic elastomer (MAH grafted SEBS), and shear at 4000r / min for 60min; then continue to add 0.3 parts of anti-aging agent (composite of UV531 and HS-944, mass ratio 1:1), keep stirring at 170°C for 30min, and prepare mixture A;

[0060] S2. At 30°C, polyurethane modified epoxy resin (EPU-133) and glycidyl ester (diglycidyl phthalate) were mixed evenly in a mass ratio of 50:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine) and aromatic amine (4,4'-dithiodiphenylamine) were mixed in a mass ratio of 70:10 to prepare a curing agent; the main agent and the curing agent were then stirred evenly to obtain a reactive resin;

[0061] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare asphalt.

[0062] The difference between Comparative Example 3 and Example 1 is that no high-density hydrogen-bonded dendritic molecules are added, and no hyperbranched epoxy resin and amino-terminated hyperbranched polyamide are added.

[0063] Comparative Example 4

[0064] S1. Heat 100 parts of road petroleum asphalt to 170°C, add 2 parts of mineral oil and 4 parts of styrene-based thermoplastic elastomer (SEBS), and shear at 4000 r / min for 60 minutes; then continue to add 0.3 parts of anti-aging agent (composite of UV531 and HS-944, mass ratio 1:1), and keep stirring at 170°C for 30 minutes to obtain mixture A;

[0065] S2. At 30°C, polyurethane modified epoxy resin (EPU-133) and glycidyl ester (diglycidyl phthalate) were mixed evenly in a mass ratio of 50:10 to prepare a main agent; long carbon chain unsaturated primary amine (cis-oleyl primary amine) and aromatic amine (4,4'-dithiodiphenylamine) were mixed in a mass ratio of 70:10 to prepare a curing agent; the main agent and the curing agent were then stirred evenly to obtain a reactive resin;

[0066] S3. At 170°C, 8 parts of reactive resin were added to mixture A and stirred for 5 minutes to prepare asphalt.

[0067] The difference between Comparative Example 4 and Example 1 is that the maleic anhydride grafted styrene thermoplastic elastomer is replaced by styrene thermoplastic elastomer, high-density hydrogen bond dendritic molecules are not added, and hyperbranched epoxy resin and amino-terminated hyperbranched polyamide are not added.

[0068] 1. The high-performance composite modified asphalt of Example 1 to Example 4 and the modified asphalt of Comparative Example 1 to Comparative Example 4 were subjected to performance tests. According to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG+E20-2011), the performance indicators of the high-performance composite modified asphalt were tested. The results are shown in Table 1:

[0069] Table 1 Technical index results of high performance composite modified asphalt

[0070] Softening point(℃) Elongation (5℃)cm Needle penetration ratio (25℃) Example 1 93.5 37.8 77.1 Example 2 95.0 34.5 77.0 Example 3 99.2 41.6 77.5 Example 4 93.9 37.1 76.8 Comparative Example 1 77.5 26.8 75.5 Comparative Example 2 77.1 25.9 75.6 Comparative Example 3 78.4 25.5 75.8 Comparative Example 4 73.9 23.9 75.2 Conventional asphalt 72.6 21.1 73.5

[0071] It can be seen from Table 1 that the high-performance composite modified asphalts prepared according to Examples 1 to 4 of the present invention show excellent performance in terms of softening point, ductility and needle penetration ratio; while the softening point, ductility and needle penetration ratio of Comparative Examples 1 to 4 are inferior to the high-performance composite modified asphalt in the examples of the present invention due to the changes in various materials, and are only slightly better than conventional asphalt.

[0072] 2. The high-performance composite modified asphalt of Example 1-Example 4 and Comparative Example 1-Comparative Example 4 were used as binders, GA10 grading median, basalt crushed stone, limestone powder, oil-stone ratio 8%, mixing temperature 215°C, mixing time 45min, to prepare a poured asphalt mixture. According to the specifications (JTG / T3364-02-2019) "Technical Specifications for Design and Construction of Highway Steel Bridge Deck Pavement", (JTG+E20-2011) "Test Procedures for Highway Engineering Asphalt and Asphalt Mixtures", etc., the 60°C penetration, -10°C bending strain, and 800 microstrain fatigue times of the above-mentioned poured asphalt mixture were tested and compared with conventional asphalt. The results are shown in Table 2:

[0073] Table 2 Technical index results of poured asphalt mixture

[0074]

[0075]

[0076] It can be seen from Table 2 that the high-performance composite modified asphalt prepared according to Examples 1 to 4 of the present invention exhibit excellent performance in terms of penetration, bending strain and fatigue resistance times; while the bending strain and fatigue resistance times of Comparative Examples 1 to 4 are inferior to the high-performance composite modified asphalt in the examples of the present invention due to the changes in various materials, and are only slightly higher than conventional asphalt.

[0077] 3. The high-performance composite modified asphalt of Example 1-Example 4 and Comparative Example 1-Comparative Example 4 were used as binders, respectively, with the median of SMA10 gradation, basalt crushed stone, limestone powder, 6% oil-stone ratio, mixing temperature of 175°C, and mixing time of 3 minutes to prepare SMA10 mixture. The 60°C dynamic stability, -10°C bending strain, and 800 microstrain fatigue times of the above SMA10 mixture were tested according to the specifications such as (JTG+E20-2011) "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results are shown in Table 3:

[0078] Table 3 Technical index results of SMA10 mixture

[0079] Dynamic stability (60℃) mm Bending strain (-10℃) Fatigue times (800 microstrain) (10,000 times) Example 1 14063 3398 175 Example 2 14027 3380 177 Example 3 16079 3495 194 Example 4 14058 3400 172 Comparative Example 1 8894 2950 136 Comparative Example 2 9102 2939 128 Comparative Example 3 8918 3021 126 Comparative Example 4 7169 2863 117 Conventional asphalt 6789 2816 108

[0080] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A high-performance composite modified asphalt, characterized in that: The modified asphalt is composed of 100 parts of road petroleum asphalt, 3-9 parts of maleic anhydride grafted styrene thermoplastic elastomer, 2-6 parts of mineral oil, 1-5 parts of high-density hydrogen bond dendritic molecules, 5-20 parts of reactive resin and 0.3-1.2 parts of anti-aging agent.

2. A high performance composite modified asphalt according to claim 1, characterized in that: The maleic anhydride grafted styrene thermoplastic elastomer is at least one of MAH grafted SEBS and MAH grafted SBS, or a mixture of the two, and the grafting rate is not less than 1.2%.

3. A high performance composite modified asphalt according to claim 2, characterized in that: The high-density hydrogen bond dendritic molecules are tannic acid with a purity of not less than 98%.

4. The high performance composite modified asphalt according to claim 1, characterized in that: The reactive resin consists of a main agent and a curing agent, wherein the main agent consists of a polyurethane-modified epoxy resin, a glycidyl ester and a hyperbranched epoxy resin in a mass ratio of 50-90:10-30:10-30; the polyurethane-modified epoxy resin is at least one of EPU-133, EPU-133L and EPU-133S; the glycidyl ester is at least one of diglycidyl phthalate, diglycidyl dimer acid, diglycidyl sebacate and diglycidyl azelaic acid; the hyperbranched epoxy resin has an epoxide value of 0.15-0.2 mol / 100g and a molecular weight of 3000-4000.

5. A high performance composite modified asphalt according to claim 4, characterized in that: The curing agent is composed of a long carbon chain unsaturated primary amine, an aromatic amine and an amino-terminated hyperbranched polyamide in a mass ratio of 70-120:10-30:10-20; the long carbon chain unsaturated primary amine is a cis-oleyl primary amine; the aromatic amine curing agent is one or more of 4,4'-dithiodiphenylamine, bis(2-aminophenyl) disulfide and 4,4'-diaminodiphenyl disulfide; the amino number of the amino-terminated hyperbranched polyamide is 3-15 mol and the molecular weight is 300-2000.

6. The high performance composite modified asphalt according to claim 1, characterized in that: The anti-aging agent is a composite of an ultraviolet absorber and a hindered amine light stabilizer, and the mass ratio of the two is 1:1; the ultraviolet absorber is at least one of UV531, UV24, UV284 or UV49; and the hindered amine light stabilizer is HS-944.

7. The high-performance composite modified asphalt according to any one of claims 1 to 6, further comprising a method for preparing the high-performance composite modified asphalt, characterized in that: The following steps are included: S1. After heating the road petroleum asphalt, add mineral oil and maleic anhydride grafted styrene thermoplastic elastomer, shear for 60-90 minutes, continue to add high-density hydrogen bond dendritic molecules and anti-aging agents, and continue stirring for 30-60 minutes, keeping the temperature at 170-185°C to prepare mixture A; S2, polyurethane modified epoxy resin, glycidyl ester and hyperbranched epoxy resin are mixed uniformly to prepare a main agent; long carbon chain unsaturated primary amine, aromatic amine and amino-terminated hyperbranched polyamide are prepared as a curing agent; the main agent and the curing agent are mixed uniformly to prepare a reactive resin; S3. Add the reactive resin into mixture A in proportion and stir for 5-15 minutes to obtain high-performance composite modified asphalt.

8. The method for preparing a high-performance composite modified asphalt according to claim 7, characterized in that: In the step S1, the road petroleum asphalt is heated to a temperature of 170-180° C.; the shear rate after adding mineral oil and maleic anhydride grafted styrene thermoplastic elastomer and mixing is 3000-4000 r / min.

9. The method for preparing a high-performance composite modified asphalt according to claim 7, characterized in that: In step S2, the mixing temperature of the main agent and the curing agent is 30-50°C.

10. The method for preparing a high-performance composite modified asphalt according to claim 7, characterized in that: In step S3, the reaction temperature of the reactive resin and the mixture A is 170-185°C.

Citation Information

Cited By

  • Asphalt regenerant and application thereof, and regeneration method of waste asphalt

    CN120098410A